2019
DOI: 10.1155/2019/4734063
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin-6 and Interleukin-15 as Possible Biomarkers of the Risk of Autoimmune Diabetes Development

Abstract: Aim The aim of our study was to assay circulating interleukin-15 (IL-15) and interleukin-6 (IL-6) levels and insulin resistance measured by two different methods in newly diagnosed autoimmune diabetes (AD) patients, their I° relatives, and healthy controls. Material and Methods The group studied consisted of 54 patients with AD (28 with Latent Autoimmune Diabetes in Adults (LADA) and 26 with type 1 diabetes (T1D)), 70 first-degree relatives, and 60 controls. IL-6, IL-15, and anti-islet antibodies concentration… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 45 publications
1
15
0
Order By: Relevance
“…Activation of M1 due to increased IL-6 expression, and IL-10 decreased [17]. In the case of diabetes mellitus, B-cell secreted pro-inflammatory cytokines are increased, and anti-inflammatory cytokines are decreased [18,19].…”
Section: Results An D Discussion Immunomodulatory Effect On Relative Nmentioning
confidence: 99%
“…Activation of M1 due to increased IL-6 expression, and IL-10 decreased [17]. In the case of diabetes mellitus, B-cell secreted pro-inflammatory cytokines are increased, and anti-inflammatory cytokines are decreased [18,19].…”
Section: Results An D Discussion Immunomodulatory Effect On Relative Nmentioning
confidence: 99%
“…The relation between microbes and diabetes is bidirectional. In other words, the high blood glucose levels complicate infections and also some microbial infections can contribute to the etiology of diabetes[ 12 - 16 ]. The undeniable role of inflammation in both diabetes and infection have been extensively portrayed, which lead to the conclusion that the use of anti-inflammatory agents can represent a rationale treatment approach for better control of diabetes or even delaying its complications.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, a 2009 study demonstrated that the treatment with IL-1Ra in patients with T2D reduced inflammatory biomarkers and improved the functioning of β cells [ 30 ]. As for the IL-15, there are few studies addressing this inflammatory biomarker and T2D, but there are some concerning the presence of high levels of this biomarker in patients with T1D [ 31 , 32 ].…”
Section: Introductionmentioning
confidence: 99%